Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.